Hubungan Pola Asuh Demokratis dengan Kecerdasan Emosional pada Remaja Akhir di Kota Jambi - Zura Azzahra; Fadzlul Fadzlul; Nurul Hafizah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
This study was motivated by the importance of emotional management skills in late adolescence, so that they are prepared to face the transition to adulthood, as well as the role of parenting styles in helping to develop these skills. The city of Jambi shows variations in the application of democratic parenting styles, which have an impact on the emotional management of adolescents. This study aims to determine how democratic parenting styles affect the level of emotional intelligence in adolescents who are approaching adulthood in the city of Jambi. This study uses a quantitative approach with a correlational design. The respondents are adolescents who have graduated from high school, aged between 18 and 21 years, and live in the city of Jambi. Democratic parenting and emotional intelligence were collected through questionnaires, then analyzed statistically to determine the relationship between variables. The study shows that the way parents treat their children with freedom and mutual respect has a positive correlation with the children's ability to manage their feelings at present. The higher the application of democratic parenting, which is characterized by warmth, open communication, responsible freedom, and consistent discipline, the higher the level of emotional.